1982
DOI: 10.3382/ps.0610414
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Scaleless Gene, sc, on Growth Performance and Carcass Composition of Broilers ,

Abstract: Two experiments were conducted in which featherless broilers (scaleless, sc/sc) were compared with feathered broilers for growth and body composition characteristics at environmental temperatures of 22, 34, and 38 C. The sc gene reduces growth and efficiency at 22 C but at 38 C the sc/sc broilers gain more, eat more, and are more efficient than feathered broilers. They achieve greater live, New York dressed, and eviscerated weights and consistently have greater eviscerated yields. The sc/sc broilers have more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

1982
1982
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 3 publications
0
11
1
Order By: Relevance
“…The increased suppressing effect of the higher temperature on feed consumption and growth in this study is quite evident. In the scaleless gene study of Somes and Johnson (1982), the comparable figures for body weight were 12.2% (34 C) and 40% (38 C) and for feed consumpltion 53.1% (34 C) and 91.7% (38 C). It is evident that the higher temperature (3 8 C) had a much greater suppressing effect on body growth of the birds in the Na gene study than it did on the birds in the sc gene study.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The increased suppressing effect of the higher temperature on feed consumption and growth in this study is quite evident. In the scaleless gene study of Somes and Johnson (1982), the comparable figures for body weight were 12.2% (34 C) and 40% (38 C) and for feed consumpltion 53.1% (34 C) and 91.7% (38 C). It is evident that the higher temperature (3 8 C) had a much greater suppressing effect on body growth of the birds in the Na gene study than it did on the birds in the sc gene study.…”
Section: Discussionmentioning
confidence: 93%
“…In the sc gene study (Somes and Johnson, 1982), carcass composition was examined only at the lower temperature (34 C). Their findings differed from those of the present study in that Somes and Johnson (1982) found significantly more protein in the hot room sc birds in both comparisons and no difference in fat on a wet basis in either comparison. Ash content was greater for the sc birds as was moisture in one comparison.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective of this line of research was to see what effect the sc gene would have on broiler growth and quality when the broilers were raised in a hot environment. Details of the development of the scaleless White Plymouth Rock broiler line, as well as data on their growth, efficiency, and carcass composition, have been previously reported (Johnson and Somes, 1978;Somes and Johnson, 1982). This report deals with the effect of the sc gene on cooked chicken and organoleptic measurements of 8-week-old broilers.…”
Section: Introductionmentioning
confidence: 91%
“…This report deals with the effect of the sc gene on cooked chicken and organoleptic measurements of 8-week-old broilers. This is part of a larger experiment that has been previously reported (Somes and Johnson, 1982).…”
Section: Introductionmentioning
confidence: 96%